Experimental Pharmacotherapy for COVID-19: The Latest Advances - Pagliano P; Scarpati G; Sellitto C; Conti V; Spera AM; Ascione T; Piazza O; Filippelli A (Dove Medical Press, 2021)
Pasquale Pagliano,1 Giuliana Scarpati,2 Carmine Sellitto,3 Valeria Conti,3 Anna Maria Spera,1 Tiziana Ascione,4 Ornella Piazza,2 Amelia Filippelli3 1Department of Medicine, Surgery and Dentistry, “Scuola Medica Salernitana”, Unit of Infectious Diseases, University of Salerno, Baronissi, Italy; 2Department of Medicine, Surgery and Dentistry, “Scuola Medica Salernitana”, Unit of Anesthesiology, University of Salerno, Baronissi, Italy; 3Department of Medicine, Surgery and Dentistry, “Scuola Medica Salernitana”, Unit of Pharmacology, University of Salerno, Baronissi, Italy; 4Department of Medicine, Service of Infectious Diseases, Cardarelli Hospital, Naples, ItalyCorrespondence: Pasquale PaglianoDepartment of Medicine, Surgery and Dentistry, “Scuola Medica Salernitana”, Unit of Infectious Diseases, University of Salerno, Via S. Allende 1, Baronissi, ItalyTel +393397504168Email ppagliano@unisa.itAbstract: The coronavirus infectious disease-2019 (COVID-19) has overwhelmed like a shock wave in a completely unprepared world. Despite coronavirus infections were involved in previous epidemic outbreaks, no antiviral agent was developed for specific treatment. As a consequence, since the beginning of this pandemic, both repositioned and experimental drugs were used to treat the infected patients without evidence of clinical efficacy. Just based on experience coming from the use of antiviral agents to treat other viruses (eg, lopinavir/ritonavir, remdesivir) and supposed antiviral or immunomodulatory activities of drugs with no approved antiviral indications (eg hydroxychloroquine, tocilizumab), clinicians have faced the ongoing pandemic. Currently, after about 9 months from the COVID-19 spread, there is still no antiviral agent capable of ensuring the cure of this syndrome. Clinical trials are beginning to confirm the benefits of some drugs, while for other compounds, efficacy and safety have not yet been confirmed. Randomized clinical trials (RCT) have denied or downsized the beneficial effects attributed to certain molecules, such as aminoquinolines, largely used in clinical practice at the beginning of COVID-19 spread. Conversely, at the same time, they have provided evidence for unexpected effectiveness of other agents that have been underutilized, such as steroids, which were not used in SARS treatment because of the threatened effect on viral replication. Evidence deriving from pathologic studies have demonstrated that the prothrombotic effects of SARS-CoV-2 can be prevented by heparin prophylaxis, underlining the need for personalized treatment for patients with severe disease. The main aim of this review is to synthesize the available information and evidence on both repositioned and experimental drugs for the treatment of COVID-19, focusing on the need to exercise caution on the use of unproven medical therapies.Keywords: SARS-CoV-2, ARDS, remdesivir, chloroquine, steroids, heparin